UJI EFEKTIVITAS FERMENTASI MOLASE SEBAGAI ANTRAKTAN NYAMUK DENGAN METODE EKSPLORASI - Imam Badrus Soleh; Ayu Septia Andriani; Siti Mulyani; Historiawati Historiawati (Universitas Tidar, 2018)
Mosquito is one of the disease-carrying vectors, one of which is dengue disease. In the control has many methods used, but in this control sometimes there are materials - materials that are not environmentally friendly and can cause resistance to the mosquito itself. The effectiveness test of molasses fermentation as a mosquito attractant by exploratory method aims to find a proportional comparison that can serve as mosquito's attractant, through the use of molasses which is a by-product of sugar cane processing and fermented using yeast (Saccharomyces cerevisae) and applied by bottle trap 1.5 L plastic that has been modified. This study lasted for 14 days. ANOVA analysis was performed on 5 treatments and 3 controls that had different comparisons and then continued with BNT (LSD) test at 1% or 5% level. The results of the analysis by filtering using 200 mesh sieve, we have found that in treatment B that is the use of 100 ml molasses + 1 gram of yeast has the highest number of mosquitoes trapped. As well as further ANOVA test results prove B treatment gives very significant different result to other treatment at LSD level 1%. These results prove that the use of effective molasses fermentation as a practical and economical mosquito attractant.